2006
DOI: 10.1104/pp.106.081208
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcript and Metabolite Profiling of Arabidopsis Leaves Reveals Fundamental Effects of the Thiol-Disulfide Status on Plant Metabolism    

Abstract: In this study, we used gas chromatography-mass spectrometry analysis in combination with flux analysis and the Affymetrix ATH1 GeneChip to survey the metabolome and transcriptome of Arabidopsis (Arabidopsis thaliana) leaves in response to manipulation of the thiol-disulfide status. Feeding low concentrations of the sulfhydryl reagent dithiothreitol for 1 h at the end of the dark period led to posttranslational redox activation of ADP-glucose pyrophosphorylase and major alterations in leaf carbon partitioning, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 62 publications
4
82
1
2
Order By: Relevance
“…These changes might be indicative of an increased mitochondrial metabolic rate in old5 mutants . Previously, it was shown that redox manipulation by DTT treatment of Arabidopsis leaves increases the level of succinate, malate, and oxaloacetate (Kolbe et al, 2006), suggesting that the changes in NAD/NADH levels may be the direct cause of the increase found in TCA cycle intermediates for the old5 mutant.…”
Section: Old5 Is Characterized By Increased Tricarboxylic Acid Cycle mentioning
confidence: 99%
“…These changes might be indicative of an increased mitochondrial metabolic rate in old5 mutants . Previously, it was shown that redox manipulation by DTT treatment of Arabidopsis leaves increases the level of succinate, malate, and oxaloacetate (Kolbe et al, 2006), suggesting that the changes in NAD/NADH levels may be the direct cause of the increase found in TCA cycle intermediates for the old5 mutant.…”
Section: Old5 Is Characterized By Increased Tricarboxylic Acid Cycle mentioning
confidence: 99%
“…Recent data suggest that upstream levels of regulation have moderate control over metabolic changes. For example, genes involved in redox regulation in Arabidopsis thaliana have quite stable expression whereas the corresponding fluxes and metabolite contents display marked genetic variations (27). Similarly, various studies on bacteria have shown that transcription is not sufficient to explain the variation of metabolic fluxes or phenotypes in Escherichia coli (28), Bacillus subtilis (29), CoFrom the ‡CNRS, UMR 0320/UMR 8120 Gé né tique Vé gé tale,…”
mentioning
confidence: 99%
“…The change in the cytosolic redox and pH status by photosynthesis could override the effect of sugar on the expression of sugar-repressive nuclear genes (49). It is possible that enzymes in addition to nitrate reductase, which is regulated by post-translational modifications (3,50,51), are regulated not only by the metabolite levels but also by the conditions of the cell. Fritz et al recently showed that amino acids did not affect each other's level (48).…”
Section: Discussionmentioning
confidence: 99%
“…Hirai et al (1) described the linkage between the levels of some secondary metabolites, such as glucosinolates and the transcripts for genes encoding corresponding metabolic enzymes. However, such approaches for the primary metabolic pathway did not give us clear information on the regulatory systems, presumably due to higher complexity (1)(2)(3).…”
mentioning
confidence: 99%
See 1 more Smart Citation